2011
DOI: 10.1200/jco.2011.36.7599
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer: A Critical Evaluation of Systemic Second-Line Therapy

Abstract: The objective of this article was to review clinical trials that used antineoplastic second-line chemotherapy and/or targeted therapies in patients with esophageal cancer after first-line therapy. Computerized (MEDLINE) and manual searches were performed to identify articles published on this topic between 1996 and 2011. Twenty-five published trials and four abstracts presented at scientific meetings were identified. A total of 10 trials included only patients with squamous cell carcinomas (SCCs), four focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 35 publications
(3 reference statements)
0
84
0
7
Order By: Relevance
“…In contrast with the first-line setting, limited data on the role of second-line therapies for OGC and PC have been historically available and, given the modest benefit of such therapies associated with the poor performance of chemorefractory patients, chemotherapy has not been routinely delivered especially in Western countries [13][14][15]. More recently, two Phase III trials showed a survival advantage for salvage chemotherapy (taxanes or irinotecan) compared with BSC [16] in chemo-refractory OGC, supporting the potential utility of salvage treatments in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the first-line setting, limited data on the role of second-line therapies for OGC and PC have been historically available and, given the modest benefit of such therapies associated with the poor performance of chemorefractory patients, chemotherapy has not been routinely delivered especially in Western countries [13][14][15]. More recently, two Phase III trials showed a survival advantage for salvage chemotherapy (taxanes or irinotecan) compared with BSC [16] in chemo-refractory OGC, supporting the potential utility of salvage treatments in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of standard second-line therapeutic regimen for patients with advanced and/or recurrent esophageal cancer (Thallinger, et al, 2011) was the reason for chosing the patients treated in the first line setting. In spite of the standard regimens recommended by NCCN guideline as combination of cisplatin and 5-Fu, TP and TPF regimens including PTX and DTX in the first line setting was settled by several studies (Petrasch, et al, 1998;Ajani, et al, 2005;, which had validated high clinical activities and survival advantages in metastatic or recurrent esophageal cancer, this superiority should not be extrapolated to Chinese patients for their different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…More than two-thirds of patients would be initially diagnosed as unresectable or metastatic disease (Thallinger, et al, 2011). Even patients with resectable disease have a high rate of recurrence with the expected median survival being only 24 months, and 5-year survival rate lower than 30% (Thallinger, et al, 2011;Mirinezhad, et al, 2014). The combination chemotherapy of 5-fluorouracil and cisplatin (PF) is the mainstay of palliative treatment for advanced or recurrent cancer (Nakajima, et al, 2013), however, their poor outcomes require urgently new researches been conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of relapse or refractory, however, data on application of second-line therapy are few, and there is no consensus on the optional second-line chemotherapy so far. Various chemotherapy combinations have been tested for second-line therapy of esophageal cancer (Grunberger et al, 2007;Yamazaki et al, 2008;Thallinger et al, 2011). Brutnwss B et al have assessed the efficiency of the combination of docetaxel and Irinotecan in cisplatin-pretreated esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%